Pengaruh peningkatan dosis kalsium terhadap tekanan darah pada ibu hamil di RSUP Dr Mdjamil Padang - Ariadi Ariadi; Syaiful Azmi; Hafni Bachtiar (Universitas Andalas, 2018)
Until recently, the exact etiology and pathophysiology of preeclampsia have not been discovered yet, but based on the clinical symptoms and the defect that appeared, researchers submitted some ways as assumption or as early detection of preeclampsia and eclampsia. Some researchers have suggested the examination of calcium / creatinine excretion ratio in urine from preeclampsia patients as the result of kidney's function changes. This study has been performed with a pre and post test group design experimental method at Obstetric and Gynecology Polyclinic in RS. Dr. M. Djamil Padang and several midwife private practices in Padang since July 2013 until the samples reached the quantity up to 40 samples. Analysis has been done to describe the relationship between calcium intake and blood pressure. Furthermore, we analyzed the differences of systolic - diastolic and MAP before and after calcium intake. Data has been shown on the table and analyzed by Pearson correlation, Wilcoxon test and Paired T test. if p <0.05, it shows a significant result. The mean of systolic after calcium intake was the same for both of the groups (121.5 + 8.02: 121.5 + 6.71). Mean of diastolic after calcium intake in controls group was lower than trials group (75.9 + 4.32: 75.9 + 4.32). Mean of MAP after calcium intake for controls group was lower that trials group (91,088 + 4.47: 91,956 + 6.08). There is an influence of calcium intake on decreasing maternal blood pressure. The mean of systolic after calcium intake was the same for both of the groups (121.5 + 8.02: 121.5 + 6.71). Mean of diastolic after calcium intake in controls group was lower than trials group (75.9 + 4.32: 75.9 + 4.32). Mean of MAP after calcium intake for controls group was lower that trials group (91,088 + 4.47: 91,956 + 6.08). There is an influence of calcium intake on decreasing maternal blood pressure. The mean of systolic after calcium intake was the same for both of the groups (121.5 + 8.02: 121.5 + 6.71). Mean of diastolic after calcium intake in controls group was lower than trials group (75.9 + 4.32: 75.9 + 4.32). Mean of MAP after calcium intake for controls group was lower that trials group (91,088 + 4.47: 91,956 + 6.08). There is an influence of calcium intake on decreasing maternal blood pressure.Keywords: Systolic, Diastolic, Mean Arterial Pressure (MAP)